Finding the Optimized Frequency of Electric Field on The Attempt ofReducing Blood Sugar Level in Type Ii Diabetes Patients - Suhariningsih, Suhariningsih; Winarni, Dwi; Husen, Saikhu Akhmad; Priyo, Tri Anggono (UI Scholars Hub, 2018)
A study has been conducted to test the use of electric fields to lower blood sugar levels on rats with type II Diabetes Mellitus. This study uses male rats (Rattus novergicus), aged 8-12 weeks weighing 150-200 grams, with a total of 31 rats. Therapy was conducted by putting rats in a chamber that emits an electric field every day for 1 hour for 28 days. To search for the optimum frequency of the treatment, frequency variations of 15, 30, 60, and 120 kHz were given. The electrical charge distribution of the air in the room was then measured, whereas mice blood sugar levels were also measured to reveal the effect of the treatment on cell tolerance to sugar, and to come up with the measurement of insulin levels at the end of the treatment. The results of measurements of the electrical charges in the air were very significant generally showing that the treatment with a frequency of 15 to 120 KHz for 4 weeks in the experimental animals could lower their blood sugar (fasting period), but the success rate significantly occurred at a frequency of 15 kHz. The decrease in fasting blood sugar levels after the treatment was probably due to the influence of the treatment (the influence of an electric field) that improved the regulation of insulin receptors. Improvements in the regulation of insulin receptor activities with high gluconeogenesis may be the cause of a decrease in fasting blood sugar levels that is not accompanied by improved cell tolerance to sugar.